1 - The “Sorbonne” of Abidjan: dream of democracy or birth of a public space? - Aghi Bahi (African Sociological Review, 2003)
Over the last few years, more or less spontaneous popular forums are developing in Abidjan. The oldest one is “La Sorbonne” in the Plateau district. It is so called in reference to the famous Parisian university. Young citizens would gather there to discuss politics. This gathering is commonly understood to be of idle persons, even by the local press. This paper contemplates the meaning of this phenomenon within the framework of the birth of the public sphere in the new context of multipartyism. Drawing on observations and interviews, the paper dwells on what takes place, and argues that the sense constructed by the actors is ‘authentic’ democracy where the individuals can freely debate politics and express their opinions. The re-invigoration of multipartyism and particularly the new constitution issued from the civilian-military transition of the year 2000 contributed towards the spread of the idea of free speech among these young males coming from popular social backgrounds. The ongoing events of Côte d’Ivoire have thrown “ La Sorbonne” and other popular forums into civil society and consider it as the obvious expression of public opinion.